Patch-Based Model for the Classification of Soybean Leaf Diseases - S., Gustavo Vigilato G.; Cavalcanti, Pablo G. (Anais do Workshop de Visão Computacional (WVC); 2021: Anais do XVII Workshop de Visão Computacional, 2021)
The disease detection is vital to increase the productivity and quality of soybean cultivation and this detection is usually carried out in a laboratory, which is time consuming and costly. To overcome these issues, there is a growing demand for technologies that aim at a faster detection and classification of diseases. In this context, this work proposes the extraction of several patches from a leaf image and combining a convolutional neural network with a support vector machine, we present a complete model for the classification of soybean leaf diseases. In this approach, an image dataset with evidence of diseases commonly observed in soybean crops was analyzed and our experiments achieved precisions greater than 90%.